Exploring the Impact of Big Data Analytics on Organizational Decision-Making and Performance: Insights from Pakistan's Industrial Sector - Latif , Assad; Fairdous, Raheela; Akhtar, Raheel; Ambreen, Muffarah (Pakistan Journal of Humanities and Social Sciences, 2023)
Little is known about how big data analytics affects decision-making and how choices have an impact on organizational performance. The research model presented in this study, which is based on the information processing view and survey-based ratings, links Big Data Analytics to organizational decision-making effectiveness and performance of organizations in Pakistan's textile industrial sector. The purpose of this paper is to examine the relationship between BDA and organizational decision-making as well as the degree to which BDA influences decision-making. Based on an adopted questionnaire, data was collected from 570 respondents. Data analysis using statistics reveals that Big Data Analytics has a favorable impact on an organization's capacity for decision-making and effectiveness. The results also show that there are no statistical differences between major firms and medium-sized businesses when it comes to the pathways from Big Data analytics to successful decision-making. Our findings advance managers' knowledge and comprehension by illuminating how Big Data Analytics might improve the effectiveness of decisions.